2021
DOI: 10.3390/molecules26030629
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Kinase Similarity in Small Molecule and Protein Structural Space to Explore the Limits of Multi-Target Screening

Abstract: While selective inhibition is one of the key assets for a small molecule drug, many diseases can only be tackled by simultaneous inhibition of several proteins. An example where achieving selectivity is especially challenging are ligands targeting human kinases. This difficulty arises from the high structural conservation of the kinase ATP binding sites, the area targeted by most inhibitors. We investigated the possibility to identify novel small molecule ligands with pre-defined binding profiles for a series … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…A structure is known to be more conserved than a sequence, and previous studies have shown that including structural information adds orthogonal information to shed light on unexpected similarities between kinases and off-target effects. , To help detect such relationships between more distantly related kinases, we generated KiSSim kinome trees based on the DFG-in conformations, as described in detail in the KiSSim Tree section, to investigate all-against-all relationships between kinases compared to the sequence-based kinome tree by Manning et al (Figure ). Note that we can base the comparison on structurally resolved kinases only, i.e., 257 out of the roughly 500 human kinases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A structure is known to be more conserved than a sequence, and previous studies have shown that including structural information adds orthogonal information to shed light on unexpected similarities between kinases and off-target effects. , To help detect such relationships between more distantly related kinases, we generated KiSSim kinome trees based on the DFG-in conformations, as described in detail in the KiSSim Tree section, to investigate all-against-all relationships between kinases compared to the sequence-based kinome tree by Manning et al (Figure ). Note that we can base the comparison on structurally resolved kinases only, i.e., 257 out of the roughly 500 human kinases.…”
Section: Resultsmentioning
confidence: 99%
“…10 The KinCore phylogenetic tree produced by a kinome-wide structure-guided MSA 7,11 overall confirms the assignment from Manning et al 6 but provides higher precision, e.g., regarding previously unassigned kinases. Schmidt et al 12 have recently investigated the similarities between a panel of nine kinasesEGFR, ErbB2, PIK3CA, KDR, BRAF, CDK2, LCK, MET, and p38abased on different pocket encodings, including the pocket sequence identity, pocket structure similarity, interaction fingerprint similarity, and ligand promiscuity. Individual kinase relationships differed according to these different perspectives, while some trends could be observed such as the atypical kinase PIK3CA being an outlier among the otherwise typical kinases in this panel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Structure is known to be more conserved than sequence, 64 and previous studies have shown that including structural information adds orthogonal information to shed light on unexpected similarities between kinases and off-target effects. 7,12 To help detect such relationships between more distantly related kinases, we generated KiSSim kinome trees based on the DFG-in conformations, as described in detail in the KiSSim tree section, to investigate all-against-all relationships between kinases compared to the sequence-based kinome tree by Manning et al 6 . Note that we can base the comparison on structurally resolved kinases only, i.e., 257 out of the roughly 500 human kinases.…”
Section: Kissim-based Kinome Treementioning
confidence: 99%
“…regarding previously unassigned kinases. Schmidt et al 12 have recently investigated the similarities between a panel of nine kinases -EGFR, ErbB2, PIK3CA, KDR, BRAF, CDK2, LCK, MET, and p38a -based on different pocket encodings, including the pocket sequence identity, pocket structure similarity, interaction fingerprint similarity, and ligand promiscuity. Individual kinase relationships differed according to these different perspectives, while some trends could be observed such as the atypical kinase PIK3CA being an outlier amongst the otherwise typical kinases in this panel.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Govindaraj and Brylinski 53 showed that docking scores tended to be more correlated in pockets binding to chemically similar ligands than in pockets binding to dissimilar ligands. This opens the possibility of estimating binding site similarity on the basis of docking rankings and enrichments, as explored by Schmidt and co-workers in their analysis of the human kinome 54 . Moreover, inverse virtual screening (i.e.…”
Section: Introductionmentioning
confidence: 99%